The Effect of Monopoly Game on the Learning Outcomes at State Islamic Senior High School Medan - Syahfitri, Nur Indah; Jamil, Khoirul (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2026)
Purpose - This research aims to analyze students' responses to the implementation of the Arabic Language Monopoly Game in the learning process and to examine the extent to which its use affects students' Arabic language learning outcomes. Design/Methodology/Approach - This research adopted a quantitative experimental approach with a one-group pretest–posttest design. The participants were assessed at two different points in time, namely before and after the implementation of the intervention. Data were collected through tests and documentation, and a sample of 32 students was selected using purposive sampling. The collected data were analyzed using descriptive statistical techniques, normality tests, and a paired-sample t-test to determine the effect of the Arabic Language Monopoly Game on students' Arabic language learning outcomes. Findings - Based on the findings, the researchers found that students showed higher learning engagement when using the Arabic language monopoly game. In addition, the average pre-test score of the students was 70.94, which increased to 84.06 in the post-test. The t-test resulted in a significance value of 0.01 < 0.05, so H₀ was rejected and H₁ was accepted, proving that the Arabic language monopoly game has an effect on the learning outcomes of class X-3 students at MAN 1 Medan. Research Limitation/Implications - This research focuses on comparing students' Arabic learning outcomes before and after using monopoly media, as well as analyzing the level of its influence.